2013
DOI: 10.1152/physiolgenomics.00013.2013
|View full text |Cite
|
Sign up to set email alerts
|

Detection of differentially methylated gene promoters in failing and nonfailing human left ventricle myocardium using computation analysis

Abstract: Human dilated cardiomyopathy (DCM) is characterized by congestive heart failure and altered myocardial gene expression. Epigenetic changes, including DNA methylation, are implicated in the development of DCM but have not been studied extensively. Clinical human DCM and nonfailing control left ventricle samples were individually analyzed for DNA methylation and expressional changes. Expression microarrays were used to identify 393 overexpressed and 349 underexpressed genes in DCM (GEO accession number: GSE43435… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
47
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 40 publications
4
47
1
Order By: Relevance
“…Emerging data show that aberrant DNA methylation patterns play an important role in cardiovascular disease, including atherogenesis (54), coronary artery disease (44,45), dilated cardiomyopathy (24), and heart failure (29,36,37). Furthermore, DNA methylation regulates the expression of myosin heavy chain 7 (Myh7), a sarcomere protein important for cardiac contractility (8).…”
mentioning
confidence: 99%
“…Emerging data show that aberrant DNA methylation patterns play an important role in cardiovascular disease, including atherogenesis (54), coronary artery disease (44,45), dilated cardiomyopathy (24), and heart failure (29,36,37). Furthermore, DNA methylation regulates the expression of myosin heavy chain 7 (Myh7), a sarcomere protein important for cardiac contractility (8).…”
mentioning
confidence: 99%
“…DNA methylation microarrays were employed to probe DNA promoters Ϫ5 kb to ϩ1 kb of gene transcriptional start sites. This approach identified regions of differential DNA methylation using 2.1 M probes, and the analysis algorithm creates peak scores that identify DNA hypermethylated and hypomethylated promoter regions (17,38).…”
Section: Resultsmentioning
confidence: 99%
“…Methylation of cytosine in CpG results from activity of DNA methyltransferases that use S-adenosylmethionine (SAM) as the requisite methyl donor. We and others previously showed that changes in cardiac DNA methylation in CM correlate with gene expression changes (17,19,(31)(32)(33). Moreover, CM in humans is associated with mitochondrial dysfunction and oxidative stress, which are characteristics of AZT toxicity and are documented in murine studies (15,16,18,23).…”
mentioning
confidence: 84%
See 2 more Smart Citations